Children with social, emotional and behavioural difficulties and communication problems : there is always a reason - Cross, Melanie (London : Jessica Kingsley Publishers, 2011)
Children and young people with social, emotional and behavioral difficulties (SEBD) are far more likely to have communication problems than their peers, yet these problems are under-recognized, under-researched, and most importantly, often unaddressed. Melanie Cross considers the reasons why behavioral and communication difficulties so often occur together, and examines the social, educational and mental health implications of this. She shows that improving the communication skills of children and young people with SEBD can contribute to better outcomes, and that speech and language therapy.
Includes bibliographical references and index.
Keywords: Communicative disorders in children; Children -- Language; Problem children -- Language; Emotional problems of children; Behavior disorders in children